Dampak Globalisasi Terhadap Pancasila Sebagai Sistem Etis Berdasarkan HAM di Indonesia - Putri Aulia Rahmi; Akbar Kurnia; Zakira Rahma; Nia Rahmadani; Nufal Ghufran Thohal Arrobi; Gina Cahyani Zamri; Sadam Rahmat (Penerbit Hellow Pustaka, 2025)
In a globalized world, human rights have become an international political good that can be exercised by international institutions and foreign countries for the administration of a country. Moral decline occurs when external values lead to bad behavior such as low self-esteem. This process brings challenges and opportunities such as cultural domination and economic disparities that affect the realization of human rights. Political ethics are influential to ensure justice and respect for individual rights in the era of globalization. International cooperation is needed to fight human rights and encourage the application of universal principles in public policy. Therefore, the Indonesian government as a member of the international community must create an ethical system that prioritizes the protection of human rights. As a result, human rights apply to every individual regardless of time and location. This human right is individual, essential and sacred. This right is also absolute, permanent and indivisible, and is an indivisible right for humanity Muhtaj, (2001: 23).